Republicanism, communism, Islam : cosmopolitan origins of revolution in Southeast Asia - Sidel, John Thayer, 1966- (Cornell University Press, 2021)
"This book provides a denationalized historical contextualization and comparative analysis of the Philippine, Indonesian, and Vietnamese revolutions. It emphasizes and evidences the importance of international circumstances and transoceanic and transcontinental cosmopolitan communities and connections-whether republican, Communist, Islamic, or otherwise- in enabling and impelling these three instances of revolutionary mobilization in Southeast Asia and in shaping their varying trajectories and outcomes"--